CULTURAL REPRESENTATION OF TORAJA ETHNIC ON THE USE OF VOCABULARY IN SINGGI’ SPEECH - Anastasia Baan; Imam Suyitno (LITERA, 2020)
The Toraja ethnic has an oral tradition of Singgi' which is passed down orally from generation to generation. This tradition is carried out at rituals, which are spoken by tradition holders or groups of people. The study outlined in this article aimed to describe the Toraja ethnic culture represented in the vocabulary in Singgi’ speech. The focus of this study was to describe the cultural dynamic and the cultural attitude of Toraja ethnic represented in vocabulary in Singgi' speech. The study was conducted through a qualitative approach using hermeneutic analysis tools. The data of this research were speech in Singgi 'and the daily context and activities of the people of Tana Toraja. The data was collected through document studies, interviews, and observations. Through qualitative analysis and hermeneutic interpretation, it was found that in Singgi’ speech, there was an absorption of vocabulary from Indonesian and old vocabulary in Toraja. The diversity of vocabulary represented that in Tana Toraja society there was a cultural dynamic that requires the Toraja language to absorb vocabulary from other languages to convey the cultural messages. Singgi' speech used old words of Toraja language that were rarely used in daily communication to convey the cultural attitudes of the Tana Toraja people. The findings showed that the vocabulary used in Singgi' speech represented the Toraja ethnic culture. This finding has important benefits in preserving the culture of the Tana Toraja community, for teaching material in the development of character education, and as a reference in developing further studies.Keywords: cultural representation, Toraja ethnic, vocabulary, Singgi’ speechREPRESENTASI BUDAYA ETNIK TORAJA PADA PENGGUNAAN KOSAKATA DALA TUTURAN SINGGI’AbstrakEtnik Toraja memiliki tradisi lisan Singgi 'yang diturunkan secara lisan dari generasi ke generasi. Tradisi ini dilakukan pada ritual, yang dituturkan oleh pemegang tradisi atau kelompok orang. Hasil kajian yang diuraikan dalam artikel ini bertujuan untuk menggambarkan representasi budaya etnik Toraja dalam penggunaan kosakata dalam tuturan Singgi’. Kajian ini memfokuskan pada pemahaman dinamika budaya dan sikap budaya etnis Toraja yang terepresentasikan pada kosakata dalam tuturan Singgi’. Penelitian dilakukan melalui pendekatan kualitatif dengan menggunakan piranti analisis hermeneutik. Data penelitian ini berupa tuturan Singgi' dan konteks perilaku kesehrian masyarakat Tana Toraja. Data dikumpulkan melalui studi dokumen, wawancara, dan observasi. Melalui analisis kualitatif dan interpretasi secara hermeneutik, ditemukan bahwa dalam tuturan Singgi’, terdapat sejumlah kosakata serapan dari bahasa Indonesia dan kosakata lama dalam bahasa Toraja. Munculnya kosakata serapan tersebut merepresentasikan bahwa dalam masyarakat Tana Toraja ada dinamika budaya sehingga mengharuskan bahasa Toraja untuk menyerap kosakata dari bahasa lain untuk menyampaikan pesan budaya. Dalam menyampaikan sikap budayanya, etnik Toraja menggunakan kosakata lama yang tidak pernah digunakan lagi dalam komunikasi keseharian masyarakat Tana Toraja. Temuan ini memiliki manfaat penting dalam melestarikan budaya masyarakat Tana Toraja, untuk bahan ajar dalam pengembangan pendidikan karakter, dan sebagai referensi dalam mengembangkan studi lebih lanjut.Kata kunci: representasi budaya, etnik Toraja, kosakata, tuturan Singgi’